2021
DOI: 10.21203/rs.3.rs-740521/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A lipid droplet-peroxisome network drives longevity by monounsaturated fatty acids via modulating ether lipid synthesis and ferroptosis

Abstract: Dietary mono-unsaturated fatty acids (MUFAs) are linked to human longevity and extend lifespan in several species1-12. But the mechanisms by which MUFAs promote longevity remain unclear. Here we show that an organelle hub involving lipid droplets and peroxisomes is critical for lifespan extension by MUFAs in C. elegans. MUFA accumulation increases lipid droplet number in fat storage tissues, and lipid droplet synthesis is necessary for MUFA-mediated longevity. Interestingly, the number of lipid droplets in you… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 112 publications
(181 reference statements)
0
3
0
Order By: Relevance
“…Another mechanism employed by cells to protect from lipid (per)oxidation involves the incorporation of less harmful MUFAs in cell membranes in order to reduce PUFA content and membrane unsaturation (Figure 3). The beneficial effect of the monounsaturated OA in the protection from lipotoxicity has been observed in many studies (Listenberger et al, 2003;Ackerman et al, 2018;Chen et al, 2018;Jarc et al, 2018;Lisec et al, 2019;Pérez-Martí et al, 2022) and more recently also linked with ferroptosis resistance (Magtanong et al, 2019;Tesfay et al, 2019;Ubellacker et al, 2020;Brunet et al, 2021;Xie et al, 2022).…”
Section: Monounsaturated Fatty Acids Lipid Peroxidation and Ferroptosismentioning
confidence: 92%
See 2 more Smart Citations
“…Another mechanism employed by cells to protect from lipid (per)oxidation involves the incorporation of less harmful MUFAs in cell membranes in order to reduce PUFA content and membrane unsaturation (Figure 3). The beneficial effect of the monounsaturated OA in the protection from lipotoxicity has been observed in many studies (Listenberger et al, 2003;Ackerman et al, 2018;Chen et al, 2018;Jarc et al, 2018;Lisec et al, 2019;Pérez-Martí et al, 2022) and more recently also linked with ferroptosis resistance (Magtanong et al, 2019;Tesfay et al, 2019;Ubellacker et al, 2020;Brunet et al, 2021;Xie et al, 2022).…”
Section: Monounsaturated Fatty Acids Lipid Peroxidation and Ferroptosismentioning
confidence: 92%
“…Despite evidence that LDs are involved in MUFA trafficking, their role in MUFA-mediated protection from ferroptosis remains unclear (Magtanong et al, 2019;Liang et al, 2022). A recent study in C. elegans provides important insights into the potential role of LDs in MUFA-regulated suppression of ferroptosis (Brunet et al, 2021). The study found that LDs are critical for MUFA-induced lifespan extension in C. elegans by forming close contact sites with peroxisomes.…”
Section: Monounsaturated Fatty Acids Lipid Peroxidation and Ferroptosismentioning
confidence: 95%
See 1 more Smart Citation